2016
DOI: 10.1039/c6ra13123a
|View full text |Cite
|
Sign up to set email alerts
|

Binaphthyl-based molecular barrier materials for phosphoric acid poisoning in high-temperature proton exchange membrane fuel cells

Abstract: In this study, thiol-functionalized binaphthyl barrier molecules were designed and synthesized for eliminating phosphoric acid (PA)-poisoning on Pt catalysts in oxygen reduction reactions (ORRs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A good interaction between the catalyst and such an organic additive can play a vital role in enhancing the efficiency and in decreasing PA poisoning of the fuel cell catalyst . Several groups examined various additives either added to the electrolyte or directly bound to the catalyst surface to improve the ORR and avoid poisoning of the Pt active sites . A recent study by Zeis and co‐workers showed that perfluoralkylated PAs used as electrolyte additives improved ORR kinetics on polycrystalline Pt .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A good interaction between the catalyst and such an organic additive can play a vital role in enhancing the efficiency and in decreasing PA poisoning of the fuel cell catalyst . Several groups examined various additives either added to the electrolyte or directly bound to the catalyst surface to improve the ORR and avoid poisoning of the Pt active sites . A recent study by Zeis and co‐workers showed that perfluoralkylated PAs used as electrolyte additives improved ORR kinetics on polycrystalline Pt .…”
Section: Introductionmentioning
confidence: 99%
“…The cyanide ions successfully prevented undesirable ions from binding at the electrode surface, allowing the ORR to proceed unhindered . Recently, Song and co‐workers investigated thiol‐functionalized binaphthyl additives to prevent phosphate species poisoning in HT‐PEMFC . They reported that the Pt catalyst was simply dipped in a terahydrofuran (THF) solution of the additive resulting in an improved ORR activity of Pt nanoparticles in the presence of PA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations